Screening Arrays of Laminin Peptides on Modified Cellulose for Promotion of Adhesion of Primary Endothelial and Neural Precursor Cells. Issue 2 (14th January 2021) - Wetzel, Richard; Hauser, Sandra; Lin, Weilin; Berg, Peggy; Werner, Carsten; Pietzsch, Jens; Kempermann, Gerd; Zhang, Yixin
Abstract: Neural precursor cells (NPC) are primary cells intensively used in the context of research on adult neurogenesis and modeling of neuronal development in health and diseased states. Substrates that can facilitate NPC adhesion will be very useful for culturing these cells. Due to the presence of laminin in basal lamina as well as their involvement in differentiation, migration, and adhesion of many types of cells, surfaces modified with laminin‐derived peptides are focused upon and compared with the widely used fibronectin‐derived Arg‐Gly‐Asp (RGD) peptides. An array of 46 peptides is synthesized on cellulose paper (SPOT) to identify laminin‐derived peptides that promote short‐term adhesion of murine NPC and human primary endothelial cells. Various previously reported peptide sequences are re‐evaluated in this work. Initial adhesion experiments show NPC preferred several laminin‐derived peptides by up to 5‐time higher cell numbers, compared to the well‐known promiscuous integrin binding RGD peptide. Importantly, screening of cell adhesion has revealed a synergetic effect of filamentous matrix, peptide sequence, surface property, ligand density, and the dynamic process of NPC adhesion. Abstract : 46 reported peptide sequences from fibronectin, laminin, and cadherins are re‐evaluated for their capacities to promote adhesion of neural precursor cells as arrays on cellulose membrane. The screening reveals a synergetic effect of filamentous matrix, peptide sequence, surface property, ligand density, and the dynamic process of cell adhesion.